Analyzing Fire Station Emergency Response with Network Analysis Tool, Kolhapur, Maharashtra (International Journal of Food and Nutritional Sciences, 2022)
This study sought to improve public safety in Kolhapur city, Maharashtra by examining theemergency response of fire stations using a Network analysis tool. The primary aim of this study was toinvestigate the reaction of fire stations in several geographical areas when faced with emergency scenarios.